Carbon Nanoparticles as Versatile Auxiliary Components of Perovskite‐Based Optoelectronic Devices. (22nd February 2021) - Litvin, Aleksandr P.; Zhang, Xiaoyu; Ushakova, Elena V.; Rogach, Andrey L.
Abstract: Metal halide perovskite‐based optoelectronics has experienced an unprecedented development in the last decade, while further improvements of efficiency, stability, and economic gains of such devices require novel engineering concepts. The use of carbon nanoparticles as versatile auxiliary components of perovskite‐based optoelectronic devices is one strategy that offers several advantages in this respect. In this review, first, a brief introduction is offered on metal halide perovskites and on the major performance characteristics of related optoelectronic devices. Then, the versatility and merits of different kinds of carbon nanoparticles, such as graphene quantum dots and carbon dots, are discussed. The tunability of their electronic properties is focused upon, their interactions with perovskite components are analyzed, and different strategies of their implementation in optoelectronic devices are introduced, which include solar cells, light‐emitting diodes, luminescent solar concentrators, and photodetectors. It is shown how carbon nanoparticles influence charge carriers extraction and transport, promote perovskite crystallization, allow for efficient passivation, block ion migration, suppress hysteresis, enhance their environmental stability, and thus improve the performance of perovskite‐based optoelectronic devices. Abstract : Carbon nanoparticles can serve as versatile auxiliary components for metal halide perovskites: they promote crystallization, passivate defects, tune charge transfer/transport characteristics, and improve the performance of perovskite‐based optoelectronic devices. This review focuses on the tunability of the electronic properties of carbon nanoparticles such as graphene quantum dots and carbon dots, analyzes their interactions with perovskite components, and introduces different strategies of their implementation in solar cells, light‐emitting diodes, luminescent solar concentrators, and photodetectors.